140k views
5 votes
Evaluate (f − g)(2) for f(x) = 2x2 − 18 and g(x) = –3x − 7.

1 Answer

5 votes

For this case we have the following functions:


f (x) = 2x ^ 2-18\\g (x) = - 3x-7

We must find:


(f-g) (2)

By definition, we have to:


(f-g) (x) = f (x) -g (x)

So:


(f-g) (x) = 2x ^ 2-18 - (- 3x-7)\\(f-g) (x) = 2x ^ 2-18 + 3x + 7\\(f-g) (x) = 2x ^ 2 + 3x-11

Then, we evaluate in x = 2:


(f-g) (2) = 2 (2) ^ 2 + 3 (2) -11\\(f-g) (2) = 2 (4) + 6-11\\(f-g) (2) = 8 + 6-11\\(f-g) (2) = 8 + 6-11\\(f-g) (2) = 3

ANswer:


(f-g) (2) = 3

User Rawr Rang
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.